The Influence of Geographical Factors on Extreme Rainfalls in Lampung Province - M Welly (Journal of Engineering and Scientific Research, 2019)
Many people in Indonesia calculate design rainfall before calculating the design flood discharge. The design rainfall with a certain return period will eventually be converted into a design flood discharge by combining it with the characteristics of the watershed. However, the lack of a network of rainfall recording stations makes many areas that are not hydrologically measured (ungauged basin), so it is quite difficult to know the characteristics of rain in the area concerned. This study aims to analyze the characteristics of design rainfall in Lampung Province. The focus of the analysis is to investigate whether geographical factors influence the design rainfall that occurs in the particular area. The data used in this study is daily rainfall data from 15 rainfall recording stations spread in Lampung Province. The method of frequency analysis used in this study is the Gumbel method. The research shows that the geographical location of an area does not have significant effect on extreme rainfall events. The effect of rising earth temperatures due to natural exploitation by humans tends to be stronger as a cause of extreme events such as extreme rainfall.